2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617226
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Luminal Contour Using Fuzzy Clustering and Mathematical Morphology in Intravascular Ultrasound Images

Abstract: An innovative application of fuzzy clustering and mathematical morphology for the problem of luminal contour detection in intravascular ultrasound images is presented. Median and standard deviation are used as features for segmentation process. Comparison was made with gold standard segmented images obtained from the average of images segmented by experienced medical doctors. Tests were carried out with 20 in vivo coronary images obtained from different patients. High correlation coefficients were found betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In recent years, researchers have tried various ways to solve this problem. Santos et al (2005) proposed a system for automatic luminal contour segmentation, it simply use Morphological filtering to get solution points obtained by linear scanner as the edge of the image, so this method cannot be applied in complex background systems. Bosworth and Acton (1999) proposed a general multi-scale mathematical morphological segmentation method but it requires some prior knowledge of the image.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have tried various ways to solve this problem. Santos et al (2005) proposed a system for automatic luminal contour segmentation, it simply use Morphological filtering to get solution points obtained by linear scanner as the edge of the image, so this method cannot be applied in complex background systems. Bosworth and Acton (1999) proposed a general multi-scale mathematical morphological segmentation method but it requires some prior knowledge of the image.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the simplicity of some of the presented works [47]- [49], [53] encouraging results were produced, especially on images acquired with low-frequency transducers (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). However, in reality, the border detection problem is more complex, especially when high-frequency transducers (above 40 MHz) are used due to intrinsic and extrinsic image artifacts (see Section I-G) as well as local and global variations among luminal and intimal grayscale distributions, demanding for more sophisticated methods.…”
Section: Statistical-and Probabilistic-based Techniquesmentioning
confidence: 99%
“…Taki et al [49] proposed a similar automated technique but used two different threshold values after despeckling through affine invariant anisotropic filters to detect both borders simultaneously. It has been shown that if distributions corresponding to lumen and tissue regions are well separated, simple decorrelation [50], thresholding techniques [51], [52], or unsupervised classification algorithms [53] along with morphological operations [52], [53] could lead to accurate identification of vessel borders.…”
Section: Statistical-and Probabilistic-based Techniquesmentioning
confidence: 99%